Las Redes Sociales como Herramientas para el Aprendizaje Colaborativo: Una Experiencia con Facebook - García Sans, Anna (Re-presentaciones: Periodismo, comunicación y sociedad, 2008)
In this work it is expected to bet on the importance of the collaborative learning in the present educational outlook, particularly in university, where there is less research about the use of TIC in the clas- sroom. Subsequently, it is described the new role of professor as a guide to the content generation. And it is introduced in the world of social networking as a support for teaching, above all by means of collaborative learning with members of a working group in Facebook. We have based our work in the practical aspects of this took through a real experience with second year students of Journalism in the Universidad Andrés Bello (Chile).
Keywords: Social networking; Facebook; Collaborative Learning; Web 2.0; Practical Application; University